A prospective randomized trial comparing piperacillin/tazobactam with meropenem as empirical antibiotic treatment of febrile neutropenic children and adolescents with hematologic and malignant disorders. Issue 6 (22nd November 2016) - Sano, Hirozumi; Kobayashi, Ryoji; Suzuki, Daisuke; Hori, Daiki; Kishimoto, Kenji; Kobayashi, Kunihiko
Abstract: Background: This randomized prospective study was designed to assess whether piperacillin/tazobactam (PIPC/TAZ) is as effective as meropenem (MEPM) as a first‐line antibiotic treatment for febrile neutropenia (FN). Procedure: FN episodes were randomly assigned to receive either PIPC/TAZ (337.5 mg/kg per day in three doses, 1‐hr DIV, maximum 13.5 g per day) or MEPM (120 mg/kg per day in three doses, 1‐hr DIV, maximum 3 g per day). Clinical responses were evaluated 120 hr after the DIV. Results: A total of 434 febrile episodes in 105 patients (42 females and 63 males) with a median age of 8 years (range 0–25) were included in this trial. Blood cultures were positive in 47 out of the 434 episodes (10.8%). Regarding responses to the treatment, success rates between the PIPC/TAZ and MEPM groups were similar (62.4 vs. 65.9%, P = 0.484), even if patients were restricted to those with bacteremia (26.1 vs 37.5%, P = 0.534). Mortality rates did not significantly differ between the two groups (0.8 vs. 0%, P = 0.500). Conclusion: Both PIPC/TAZ and MEPM appeared to be equally efficacious and safe. Carbapenems are now broadly used to treat FN; however, this may increase the prevalence of drug‐resistant bacteria. In this regard, the treatment using PIPC/TAZ for FN is more beneficial.